Situation of Dental Caries and Periodontal Disease of people who get services in Kongkrailas hospital, Sukhothai province - สุวรรณนพรัตน์ นภา (Community and Social Development Journal, 2019)
This research aims to study Situation of Dental Caries and Periodontal Disease of people who get services in Kongkrailas hospital, Sukhothai province that analyzed secondary data in HosXP program of Kongkrailas hospital during October 1, 2016 to September 30, 2018 in dental services of people. The collected data was analyzed by frequency (percentage). Year 2016 – 2018, the upward trend of dental services of people were 4,448 persons, 4,669 persons and 5,185 persons respectively. But the early dental caries of people were 8.99%, 0.34%, 0.15% respectively and the gingivitis was 14.21%, 13.64%, 9.82% respectively and the periodontitis was 13.35%, 11.09% and 10.20% respectively. Year 2017, the most of people’ dental services were filling (25.51%), scaling (24.65%), wearing dentures (8.12%) and tooth extraction (26.29%), coated fluoride (10.47%), dental sealant (11.48%) respectively in year 2018. The analytical of age groups, the most of dental caries without treatment in the studying and teenage group as 48.72% and the elderly group had the most of the periodontitis problem as 21.45%. Therefore, the hospital officer should cooperate with the public health networks and communities to coordinate planning, announce and educate people each group in correct dental care to protect dental caries and periodontal disease.